DISTINGUISHING BETWEEN SUKUK AND CONVENTIONAL BOND FOR HALAL INVESTMENT - Noriza Mohd Saad; NorEdi Azhar Mohamad; Zulkifli Mohamed (International Journal of Accounting, Finance and Business, 2023)
This paper are motivated to reviews, discuss and proposed a valuations technique for sukuk as opposed to conventional bonds since it is considering a relatively new in the capital market. The discussion on capital market history and developments encompassing sukuk trading mechanism, especially in Malaysia is significantly contribute to the halal investment follows shariah compliance. We have seen the importance of sukuk in contemporary finance as an alternative the traditional practice of seeking financing from banks. Bonds were introduced to finance major investments with greater flexibility to accommodate the changing landscape and dynamism of international finance. With the growth in demand for Islamic financial alternatives, sukuk were introduced which has led to greater financial inclusion and has contributed towards unifying the conventional and Islamic frameworks of finance. Since, sukuk investment applies the halal theory in not only this investment financing product but also the way of dealing with cost charging and how to manage and monitors the investment performance based on Islamic principles. Sukukholders demand halal investment to achieve Maqasid Al-Shariah encourage the issuer to offer or issue sukuk. In Islam, halal investment is compulsory for all Muslims.